Political Connections Impact on Corporate Governance Quality - Sandy Harianto (Universitas Prasetiya Mulya, 2022)
The paper explores political connections impact on corporate governance quality in Indonesia. Using data from publicly listed firms in Indonesia stock exchange for the 2010-2019 period, this study find that politically connected firms are actually having better corporate governance quality than their counterparts. The significant development on corporate governance system implementation and changes in political system may influence the political connections impact on corporate governance quality. Additionally, the findings also indicates that the political connections improve board efficiency, risk management and stakeholders relationship. The findings from this study is markedly dissimilar from previous studies that emphasize on the rent-seeking nature of political connectedness. Institutional setting changes such as the changes in political system and coporate governance system may changes the nature of politically connected firms to become more responsible. The results maybe of interests for regulators of emerging countries around the world and shed a new paradigm on political connectedness. The findings of the papers indicates that the design of regulatory frameworks and policies should consider the potential positive effects of political connections, rather than simply focusing on potential drawbacks. The results indicate that promoting political connections that are accountable and transparent can be beneficial for the investment environment.